Playing Dota 2: professional careers in e-sports = Grając w Dota 2: kariery zawodowe w e-sporcie - Nyćkowiak, Justyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Playing video games, especially the e-sports ones, is one of new professional activities, particularly popular among young people. The analysis presented in this article focuses primarily on the objective dimension of professional careers and uses the conceptual framework of various disciplines. The results show that the application of specific professional development strategies in e-sport requires making individual choices of patterns and paths adapted to intensive social and technological changes. In the case of e-sport players` careers, the pace of changes largely determines the possibilities of planning and pursuing specific career paths. This situation is favourable to the people who not only represent a professional level of skills in playing an e-sports game, but also have the soft skills that enable an intentional and thoughtful management of their profession career paths.
Keywords: e-sport; professional career; e-sports players` careers; DOTA 2; kariera zawodowa; e-sportowe kariery zawodowe